Evaluation of Mutual Cooperation Characters in Kindergarten (TK) Students: A Preliminary Study: Evaluasi Karaker Gotong Royong Pada Siswa Taman Kanak-Kanak (TK): Sebuah Studi Awal - Devina, Feri; Nurdin, Encep Syarief; Ruyadi, Yadi; Kosasih, Aceng (Pendidikan Guru PAUD Universitas PGRI Semarang, 2025)
Abstract The main issue in this research is the lack of understanding and deep habituation of essential character values. The purpose of this study was to evaluate the character of mutual cooperation in kindergarten students in Bandung City, Indonesia. The methodology of this research uses quantitative methods and quasi-experimental techniques. The research design adopted is the non-equivalent pretest-posttest Post-test Control Group Design. Data were collected using a Likert scale questionnaire given to the students' parents. This questionnaire measures the components of mutual cooperation. A total of 26 respondents from School A and 18 respondents from School B participated in this study. The analysis results show that the character of mutual cooperation is already possessed by students in both schools. The average score for mutual cooperation is 1.77 (SD = 1.107) in School A and 1.50 (SD = 0.786) in School B. However, these values need to be improved. This research recommends the use of the traditional Papancakan game to strengthen the character of mutual cooperation. The integration of local cultural wisdom into the early childhood education curriculum is very important for the development of children's character. Keywords: Early Childhood Education; Kindergarten; Character Education; Mutual Cooperation Abstrak Permasalahan utama dalam penelitian ini tentang kurangnya pemahaman dan pembiasaan yang mendalam tentang nilai-nilai esensi karakter. Tujuan penelitian ini untuk mengevaluasi karakter gotong royong pada siswa TK di Kota Bandung, Indonesia. Metodologi penelitian ini menggunakan metode kuantitatif dan teknik kuasi eksperimen. Desain penelitian yang diadopsi adalah Non-equivalent Pre-test Post-test Control Group Design. Data dikumpulkan menggunakan kuesioner skala Likert yang diberikan kepada orang tua siswa. Kuesioner ini mengukur komponen gotong royong. Sebanyak 26 responden dari Sekolah A dan 18 responden dari Sekolah B berpartisipasi dalam penelitian ini. Hasil analisis menunjukkan bahwa karakter gotong royong sudah dimiliki oleh siswa di kedua sekolah. Skor rata-rata untuk gotong royong, skor rata-rata adalah 1.77 (SD = 1.107) di Sekolah A dan 1.50 (SD = 0.786) di Sekolah B. Namun, nilai-nilai tersebut perlu ditingkatkan. Penelitian ini merekomendasikan penggunaan permainan tradisional Papancakan untuk memperkuat karakter gotong royong. Integrasi kearifan budaya lokal dalam kurikulum pendidikan anak usia dini sangat penting untuk perkembangan karakter anak. Kata kunci: Pendidikan Anak Usia Dini; Taman Kanak-Kanak; Pendidikan Karakter; Gotong Royong